Enhancement Campus Office Supplies Requests Website Utilizing Rapid Application Development - Setiawan, Jovanka Suryajaya; Oetama, Raymond Sunardi; Andersen, James (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
The web-based office supplies requisition application is a significant step in modernizing office equipment procurement in various organizations, including universities. However, this website encounters problems due to immature planning and less effective implementation. The current website faces some problems with requesting office supplies on campus, where the current process lacks efficiency and transparency in the status of user requests. It often results in discrepancies between the registered stock of office supplies and the actual stock in the warehouse. Our research aims to improve this website using the Rapid Application Development methodology. We also include user feedback when designing this website. The result is a new web-based application that provides a much better user experience when requesting office supplies. This update is expected to increase the efficiency of office equipment request services, provide users with more transparent request status information, and ensure accurate stock availability.